Gait analysis may help to distinguish hereditary spastic paraplegia from cerebral palsy - Wolf, Sebastian Immanuel; Braatz, Frank; Metaxiotis, Dimitrios; Armbrust, Petra; Dreher, Thomas; Döderlein, Leonhard; Mikut, Ralf (Gait & posture, 2011)
Hereditary spastic paraplegia (HSP) designates a group of genetic disorders typically leading to spasticity in the lower limbs and consequently to gait disorders. Although the symptoms are similar to those of cerebral palsy (CP), the correct diagnosis is important for treatment recommendations as one condition is progressive in nature whereas the other is not. Due to the heterogeneity of HSP, genetic testing is complex and in some genetic forms still not possible. The aim of this study was, therefore, to investigate if instrumented 3D-gait analysis could help distinguish between these two conditions. The gait pattern of 29 patients with HSP was compared with that of 29 patients with CP who were matched in age, sex, and the extent of gait disturbance and also to 29 typically developing subjects for reference. More than 3000 gait parameters were evaluated for their relevance to classify patients into diagnostic groups. Cluster analysis revealed that these gait features may classify only subgroups of symptoms as the gait pattern is very heterogeneous within each diagnosis group. However, prolonged hip extension, knee extension, and ankle plantar flexion were identified as indicators for HSP. In addition, large trunk tilt velocities appear unique in some cases of HSP. These indicators in gait pattern may contribute in establishing the diagnosis of HSP, which is important in predicting outcome when planning surgical treatment for functional improvements in these patients.